Development of an AI-Based Differentiated Learning Module for Quran-Memorizing Students to Enhance Mathematics Achievement and Motivation in Elementary Education - Achmad, Novianita; Hulukati, Evi; Pomalato, Sarson W.; Djafri, Novianty (PPSDP International Journal of Education, 2024)
Quran-memorizing students face unique challenges in balancing their religious memorization with academic subjects, particularly mathematics. This study aims to develop an AI-based differentiated learning module tailored to the specific needs of Quran-memorizing elementary students to improve their mathematics performance and motivation. The module was designed to personalize content delivery and provide real-time feedback to enhance student engagement. Using the ADDIE model as the research methodology, the study involved analyzing student needs, designing, developing, implementing, and evaluating the module. The results showed a significant improvement in both academic performance and student motivation in learning mathematics. The AI-based module allowed for a more interactive, adaptive, and personalized learning experience, addressing the diverse learning profiles of students. This research contributes to the growing field of AI in education, demonstrating the potential of differentiated learning approaches to enhance academic outcomes. Future studies should explore the long-term effectiveness of such modules and consider expanding their application to other subjects and student groups.